Perspectives on the Self Reflexivity in the Humanities - Matějčková, Tereza; Kolman, Vojtěch (De Gruyter, 2022)
The volume develops the concepts of the self and its reflexive nature as they are linked to modern thought from Hegel to Luhmann. The moderns are reflexive in a double sense: they create themselves by self-reflexivity and make their world - society - in their own image. That the social world is reflexive means that it is made up of non-subjective (or supra-subjective) communication. The volume's contributors analyze this double reflexivity, of the self and society, from an interdisciplinary perspective, focusing both on individual and social narratives. This broad, interdisciplinary approach is a distinctive mark of the entire project. The volume will be structured around the following axes: Self-making and reflexivity - theoretical topics Social self and the modern world Literature - self and narrativity Creative Self - text and fine art. Among the contributors are some of the most renowned specialists in their respective fields, including J. F. Kervégan, B. Zabel, P. Stekeler-Weithofer, I. James, L. Kvasz, H. Ikäheimo and others.